SSR analysis of genetic changes during artificial ageing of rice seeds stored under gene bank management - Adeboye , K. A.; Adabale , O. W.; Adetumbi , J. A.; Ayo-Vaughan, M. A.; Daniel , I. O. (Plant Breeding and Seed Science, 2015)
Two experiments were conducted to evaluate ageing-induced genetic changes and to establish physiological thresholds for loss of genetic integrity during ageing or storage of rice seeds. In the first experiment, seeds of 10 varieties of rice were subjected to artificial ageing in chambers conditioned to 55°C and 72±2% RH for 72 hours. In the second experiment, seeds of 4 varieties of rice stored in the NACGRAB gene bank, Nigeria in 2011 at 5± 4°C were compared with seeds of the same accessions freshly harvested in 2013. Data were collected on seed germination and seedling length to estimate the seed vigour index. Genetic changes during the ageing were evaluated by SSR markers using a Direct™ PCR kit. Genetic distance indices were computed using PAST™ software and percentage genetic integrity was estimated from the genetic distance matrices. At 72 hours of artificial ageing, seed germination percentage declined to 54.2% and vigour index 0.8 coinciding with the lowest estimate of genetic integrity of 99.5%. The decline in percentage genetic integrity during the artificial ageing indicated a systematic ageing-induced genetic alteration. SSR primer RM178 revealed variations that suggest losses of alleles in the course of ageing for 2 accessions at between 24 hours in WITA4 and 48 to 51 hours in CG14. In the gene bank storage trial, germination of seeds after one and two years of storage was above 80% and there were no significant differences among the accessions. SSR profiles for all the accessions were also similar. The result partly corroborates the artificial ageing data. This implies that seed viability benchmark of 54% is recommended for regeneration of stored rice seeds in order to maintain optimum genetic integrity during storage.